Do customized fiberglass posts influence the bond interface in different regions of intraradicular dentin? - Godas, André Gustavo de Lima [UNESP]; Suzuki, Thaís Yumi Umeda; Gomes Filho, João Eduardo [UNESP]; Assunção, Wirley Gonçalves [UNESP]; Sundfeld, Renato Herman [UNESP]; Briso, André Luiz Fraga [UNESP]; dos Santos, Paulo Henrique [UNESP] (Taylor & Francis, 2020)
This study evaluated the push-out bond strength of customized glass fiber posts in different regions of post space (cervical, middle and apical) submitted to mechanical cycling. Forty single-rooted human premolar teeth were submitted to endodontic treatment and divided into four groups, according to the type of fiberglass posts installed: customized or non-customized posts. Half of the samples were submitted to 1,200,000 mechanical cycles. Samples sections of approximately 1.3 mm thickness were obtained from each regional third and the samples were subjected to push-out bond test. Data were analyzed by two-way repeated measures ANOVA and Tukey's test (p = 0.05). There was no statistically significant difference between customized and non-customized fiberglass posts at the cervical region, regardless if the mechanical cycling was performed. (p = 0.18). In the middle third, the highest value of bond strength was observed in the non-customized group without mechanical cycling (12.90 ± 6.88 MPa), but it was not significantly different from the respective aged group (7.58 ± 4.72 MPa) (p > 0.05). Similar results observed in the apical region, where lower values were found for the customized groups. For customized fiberglass posts, the cervical region showed higher values of bond strength compared to the middle and apical thirds (p < 0.05) with or without mechanical cycling. The customization of fiberglass posts is not an essential clinical procedure since it does not improve the bond strength of fiberglass posts to dentin, independent of the mechanical cycling procedure.
Keywords: Dentin; glass fiber post; push-out strength; resin cement